Lithium battery positive electrode material, preparation method thereof and lithium battery

By covering the carbon layer on the lithium iron phosphate positive electrode material and optimizing its XRD spectrum characteristic peak area, the problem of charging and discharging imbalance in the charging and discharging process is solved, and the excellent charging and discharging performance and energy efficiency of lithium batteries are achieved.

CN119627070APending Publication Date: 2025-03-14XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411746964.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The lithium iron phosphate positive electrode material has a charging and discharge imbalance problem during the charging and discharging process, which leads to an increase in the energy consumption of the battery during use and hinders its application in lithium batteries.

Method used

The electronic conductivity and lithium ion conductivity of the material are optimized by coating a carbon layer on lithium iron phosphate materials and using specific differential XRD spectrum parameter ranges (17.0-17.5°, 18.0-18.3°, 20.5-21.1°, 25.4-26.2°).

Benefits of technology

The balanced charging and discharging performance of the positive electrode material of lithium battery is achieved, the DCR difference between the positive electrode material in the same state of SOC during the charging and discharging process is reduced, and the charging and discharging performance and energy efficiency of the lithium battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627070A_ABST
    Figure CN119627070A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and provides a lithium battery positive electrode material, a preparation method thereof and a lithium battery. The lithium battery positive electrode material comprises a lithium iron phosphate material with a carbon coating layer, and in a differential XRD (X-Ray Diffraction) spectrogram of the lithium battery positive electrode material, the sum of the absolute values of the peak areas of characteristic peaks between 17.0-17.5 degrees and 18.0-18.3 degrees is 0.043-0.060, the sum of the absolute values of the peak areas of characteristic peaks between 20.5-21.1 degrees is 0.030-0.065, and the sum of the absolute values of the peak areas of characteristic peaks between 25.4-26.2 degrees is 0.050-0.090. The lithium battery positive electrode material can effectively solve the problem that the DCR difference is large in the same SOC state in the charging and discharging process of a lithium battery, and the energy consumption of the lithium battery in use is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and specifically provides a lithium battery positive electrode material and a preparation method thereof, and a lithium battery. Background Art

[0002] In recent years, with the rapid development of electric vehicles, smart grid energy storage and other fields in my country, lithium-ion batteries have been widely used in various fields. Among them, lithium iron phosphate positive electrode materials are stable and do not decompose, and the batteries made of them have safety that other positive electrode material systems cannot match. In addition, lithium iron phosphate batteries have long cycle life, abundant raw material resources, and low cost, and are the focus of research and industrial development in the field of power and energy storage lithium batteries.

[0003] However, due to the olivine structure of lithium iron phosphate materials, which is different from the layered transition metal oxide structure of traditional positive electrode materials, its lithium ion diffusion channel is one-dimensional, and the poor electronic conductivity and low lithium ion diffusion rate of lithium iron phosphate materials themselves lead to poor DC resistance (DCR) performance and related rate and low temperature performance of this type of material. In recent years, methods such as carbon element coating, metal doping, and nano-sizing have been developed to improve the electrochemical properties of lithium iron phosphate. However, lithium iron phosphate positive electrode materials still have the problem of charge and discharge imbalance, which leads to increased energy consumption of the battery during use, which also hinders the application of lithium iron phosphate materials in lithium batteries. Summary of the invention

[0004] In view of the above problems existing in the prior art, the object of the present invention is to provide a lithium battery positive electrode material and a preparation method thereof and a lithium battery.

[0005] In a first aspect, the present invention provides a positive electrode material for a lithium battery, wherein the positive electrode material for a lithium battery comprises a lithium iron phosphate material having a carbon coating layer, and in a differential XRD spectrum of the positive electrode material for a lithium battery, the sum of the absolute values ​​of the peak areas of characteristic peaks between 17.0-17.5° and 18.0-18.3° is 0.043-0.060, the sum of the absolute values ​​of the peak areas of characteristic peaks between 20.5-21.1° is 0.030-0.065, and the sum of the absolute values ​​of the peak areas of characteristic peaks between 25.4-26.2° is 0.050-0.090;

[0006] The method for obtaining the differential XRD spectrum is:

[0007] S1, assembling the positive electrode sheets containing the positive electrode material of the lithium battery into two groups of batteries, namely battery I and battery II;

[0008] S2, at 25°C, charge and discharge the battery I and the battery II for the first cycle, and continue to charge to 100% SOC, then discharge the battery I to 50% SOC, and discharge the battery II to 0% SOC, to obtain the battery I and the battery II after load adjustment;

[0009] S3, performing XRD tests on the positive electrode plates in the battery I and the battery II after charge adjustment, respectively, to obtain XRD spectra of the plates;

[0010] S4, performing background subtraction and normalization processing on the pole piece XRD spectrum, subtracting the pole piece XRD spectrum of battery I from the pole piece XRD spectrum of battery II to obtain a differential XRD spectrum.

[0011] In the lithium battery positive electrode material provided by the present invention, the lithium iron phosphate material is coated with carbon, which helps to improve the electronic conductivity of the material and thus improve the lithium ion conductivity. In addition, the lithium battery positive electrode material that meets the above parameters has balanced charging and discharging performance, which can effectively solve the problem of large differences in DCR of positive electrode materials under the same SOC state during the charging and discharging process of lithium batteries, so that the prepared lithium battery has excellent charging and discharging performance.

[0012] In a second aspect, the present invention provides a method for preparing the positive electrode material of a lithium battery according to the first aspect of the present invention, the preparation method comprising: mixing and sintering positive electrode material A and positive electrode material B at a mass ratio of 100:(10-20) to obtain the positive electrode material of a lithium battery; wherein,

[0013] The positive electrode material A is a lithium iron phosphate material with a carbon coating layer prepared by a solid phase method.

[0014] The positive electrode material B is a lithium iron phosphate material with a carbon coating layer prepared by a liquid phase hydrothermal method.

[0015] In a third aspect, the present invention provides a lithium battery, comprising the lithium battery positive electrode material described in the first aspect of the present invention.

[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0018] Figure 1 The differential XRD spectrum of the lithium battery positive electrode material prepared in Example 1;

[0019] Figure 2The differential XRD spectrum of the lithium battery positive electrode material prepared in Example 2;

[0020] Figure 3 The differential XRD spectrum of the positive electrode material A1 prepared in Comparative Example 1;

[0021] Figure 4 This is the differential XRD spectrum of the positive electrode material B1 prepared in Comparative Example 2. DETAILED DESCRIPTION

[0022] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0023] The "range" disclosed in the present invention is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit. The range defined in this way includes end values ​​and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form an unambiguous range, and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. Each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range. In addition, the scope of the expression "between AB" includes the A endpoint and the B endpoint itself.

[0024] In the present invention, the terms "first" and "second" are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. In addition, the meaning of "multiple" is two or more.

[0025] In the present invention, the terms "optionally" and "optional" mean that the event or environment described later can but does not have to occur. For example, "optional M source" means that the M source can be used or not used, which includes: using the M source and not using the M source.

[0026] In the present invention, the terms "sintering", "first sintering" and "second sintering" describe different environments. "Sintering" is aimed at preparing the positive electrode material of the lithium battery. The first sintering is aimed at the preparation of positive electrode material A, and the second sintering is aimed at the preparation of positive electrode material B.

[0027] In addition, unless otherwise specified, all embodiments and optional embodiments of the present invention may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present invention.

[0028] The inventors of the present invention have found that the traditional lithium iron phosphate materials have phase separation of lithium-rich phase and lithium-poor phase during the charging and discharging process, resulting in differences in the phase change process of charging and discharging, leading to changes in the interface and bulk phase composition, resulting in significant differences in the discharge impedance and charging impedance of the lithium battery. Even under the premise of reducing the discharge impedance as much as possible, the charging impedance is still maintained at a high level, making the energy consumption of the lithium battery during the charging process too high. Further, starting from this perspective, the present invention proposes a new lithium battery positive electrode material by studying the relationship between factors such as material structure and the phase change process and polarization level during the charging and discharging process, so as to solve the problem of poor balance of charging and discharging performance caused by the phase change process characteristics of the structure of lithium iron phosphate materials during the charging and discharging process.

[0029] A first aspect of the present invention provides a lithium battery positive electrode material, which includes a lithium iron phosphate material with a carbon coating layer, and the lithium battery positive electrode material also satisfies the following characteristics: in a differential XRD spectrum, the sum of the absolute values ​​of the peak areas of the characteristic peaks between 17.0-17.5° and 18.0-18.3° is 0.043-0.060, the sum of the absolute values ​​of the peak areas of the characteristic peaks between 20.5-21.1° is 0.030-0.065, and the sum of the absolute values ​​of the peak areas of the characteristic peaks between 25.4-26.2° is 0.050-0.090.

[0030] In the present invention, in the XRD spectrum and differential XRD spectrum of the positive electrode material of the lithium battery, the horizontal axis represents 2θ, and the vertical axis represents the relative intensity normalized by the strongest peak intensity. The characteristic peaks existing between 2θ of 17.0-17.5° and 18.0-18.3° can reflect the changes of the (200) crystal planes of the lithium-rich phase and the lithium-poor phase of the lithium iron phosphate material during the phase change process, the characteristic peaks existing between 20.5-21.1° can represent the changes of the (101) crystal plane of this type of material, and the characteristic peaks existing between 25.4-26.2° can represent the changes of the (111) crystal plane of this type of material. In the differential XRD spectrum, the absolute value of the peak area of ​​each characteristic peak can reflect the phase change process of the positive electrode material during charging and discharging.

[0031] In the present invention, a differential XRD spectrum is obtained by following steps S1 to S4:

[0032] S1, assembling positive electrode sheets containing positive electrode materials of lithium batteries into two groups of batteries, namely battery I and battery II;

[0033] S2, at room temperature (25°C), the battery I and the battery II are charged and discharged for the first cycle, and are continuously charged to 100% SOC, and then the battery I is discharged to 50% SOC, and the battery II is discharged to 0% SOC, to obtain the battery I and the battery II after load adjustment;

[0034] S3, performing XRD tests on the positive electrode plates in the battery I and the battery II after charge adjustment, respectively, to obtain XRD spectra of the plates;

[0035] S4, performing background subtraction and normalization processing on the pole piece XRD spectrum, subtracting the pole piece XRD spectrum of battery I from the pole piece XRD spectrum of battery II to obtain a differential XRD spectrum.

[0036] The present invention does not particularly limit the preparation method of the positive electrode plate to be tested in step S1. For example, the positive electrode slurry containing the positive electrode material of the lithium battery, the conductive agent, the binder and the solvent can be coated on the positive electrode collector (such as aluminum foil, carbon-coated aluminum foil, etc.), and then dried to form a positive electrode film layer to obtain the positive electrode plate.

[0037] In some embodiments, the two assembled battery groups are half-button batteries, and the negative electrode plates of the half-button batteries can be lithium plates.

[0038] In step S2, the chemical reaction inside the battery can be activated through the first cycle of charge and discharge to form a stable electrochemical structure.

[0039] As some examples, the process in step S2 includes: at 25°C, charging battery I and battery II at a constant current rate of 0.1C to 4.2V (vs Li), charging at a constant voltage at a potential of 4.2V (vs Li) to a cutoff rate of 0.02C, and discharging at a constant current rate of 0.1C to 2.5V (vs Li); charging battery I and battery II that have completed the first cycle of charge and discharge at a constant current rate of 0.1C to a cutoff voltage of 4.2V (vs Li), and then charging at a constant voltage at a potential of 4.2V (vs Li) to a cutoff rate of 0.02C; then discharging battery I at a constant current rate of 0.1C to 50% SOC, and discharging battery II at a constant current rate of 0.1C to SOC 0%, to obtain battery I and battery II after load adjustment.

[0040] In some embodiments, the operation of step S3 includes: disassembling the battery I and the battery II after charge adjustment to obtain the positive electrode sheet, washing the positive electrode sheet with an organic solvent, vacuum drying, and then performing an XRD test.

[0041] In step S3, it is preferred to disassemble the battery within 30 minutes to obtain the positive electrode plate to be tested, so that the phase structure of the positive electrode material in the plate can be kept in a charge adjustment state.

[0042] In step S3, the organic solvent can be selected according to the electrolyte in the assembled battery, for example, it can be selected from carbonate solvents, carboxylic acid ester solvents, etc. According to some embodiments, the organic solvent is selected from one or more of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), propylene carbonate (PC), and ethylene carbonate (VC).

[0043] In some embodiments, the vacuum drying temperature is 20-40° C., such as room temperature.

[0044] As some examples, the XRD test conditions include: using Cu-kα as the radiation source, angle range: 10°-80°, step size The dwell time for each step is 0.3 s.

[0045] In step S4, the background subtraction and normalization of the pole piece XRD spectrum can be performed using TOPAS software. As a specific example, the operation of using TOPAS software for background subtraction and normalization includes importing the XRD spectrum of the pole piece into the software, performing background subtraction, selecting the background fitting parameter (Background), setting the polynomial order (Order) to 4, importing the instrument parameters in the instrument parameter (Instrument) task bar, and selecting the sample height correction (Sample displacement) in the error correction parameter (Corrections).

[0046] Furthermore, the corresponding characteristic peaks in the differential XRD spectrum are integrated to calculate the peak area, and the absolute values ​​of the peak areas are added together.

[0047] It should be understood that the relative intensity (ordinate) of the characteristic peak of the differential XRD spectrum has positive and negative numbers, and the integration of each characteristic peak is divided horizontally (in the direction of the abscissa) at the ordinate of 0, and the peak area is taken for the characteristic peak above the ordinate of 0 (the peak area is a positive number, i.e., equal to its absolute value), and the peak area is taken for the characteristic peak below the ordinate of 0 (the peak area is a negative number). In addition, when the peak area is a negative number, the "sum of the absolute values ​​of the peak areas" refers to taking the absolute value of the characteristic peak with a negative peak area and then adding it to the peak area (positive number) of other characteristic peaks.

[0048] In the present invention, the lithium iron phosphate material may be lithium iron phosphate (LFP) or metal-doped lithium iron phosphate. According to some embodiments, the general chemical formula of the lithium iron phosphate material is LiFe x M 1-x PO4, 0.98≤x≤1.0, M represents a doping element, specifically selected from one or more of Mn, F, Al, Ti, Zr, Co, Zn and V.

[0049] Preferably, the lithium iron phosphate material is LiFePO4 and LiFe 0.995 V 0.005 (PO) or more.

[0050] In some embodiments, in the differential XRD spectrum of the lithium battery positive electrode material, the sum of the absolute values ​​of the peak areas of the characteristic peaks between 17.0-17.5° and 18.0-18.3° is 0.043-0.055, the sum of the absolute values ​​of the peak areas of the characteristic peaks between 20.5-21.1° is 0.032-0.058, and the sum of the absolute values ​​of the peak areas of the characteristic peaks between 25.4-26.2° is 0.051-0.085.

[0051] In the present invention, the lithium iron phosphate material is coated with carbon to effectively improve the conductivity of the lithium iron phosphate material. It should be understood that the lithium iron phosphate material with a carbon coating layer means that at least part of the surface of the lithium iron phosphate material is coated with carbon material.

[0052] The second aspect of the present invention provides a method for preparing the positive electrode material of a lithium battery according to the first aspect of the present invention, comprising: mixing and sintering positive electrode material A and positive electrode material B in a mass ratio of 100:(10-20) to obtain the positive electrode material of a lithium battery.

[0053] [Positive electrode material A]

[0054] In the present invention, the positive electrode material A is a lithium iron phosphate material with a carbon coating layer prepared by a solid phase method. The positive electrode material A prepared by the solid phase method has larger grains and better sphericity, which is beneficial to improving the life of the lithium battery.

[0055] In some embodiments, the method for preparing the positive electrode material A includes: uniformly mixing iron phosphate, a first lithium source, a first carbon source, water and an optional M source, grinding and drying, and then performing a first sintering to obtain the positive electrode material A; wherein the M source is selected from one or more of a Mn source, a F source, an Al source, a Ti source, a Zr source, a Co source, a Zn source and a V source.

[0056] In the present invention, the first lithium source may be a conventional choice when preparing lithium iron phosphate by solid phase method. From the perspective of easy availability of raw materials, the first lithium source is preferably at least one of lithium carbonate and lithium hydroxide.

[0057] In the present invention, the first carbon source can be decomposed to form a carbon material during the first sintering process. According to some embodiments, the first carbon source is selected from one or more of glucose and polyethylene glycol (PEG). Specific examples of polyethylene glycol include but are not limited to PEG6000, PEG8000, etc.

[0058] Preferably, the first carbon source is glucose and PEG6000.

[0059] More preferably, the mass ratio of glucose to PEG6000 is (2-5):1, such as 2:1, 3:1, 3.2:1, 3.5:1, 4:1, etc.

[0060] In some embodiments, the mass ratio of the first carbon source to ferric phosphate may be (8-15):100, for example, 8:100, 9:100, 10:100, 11:100, 12:100, 14:100, etc.

[0061] As some examples, the M source may be selected from one or more of vanadyl sulfate, manganese sulfate, aluminum fluoride, titanium oxalate, zirconium sulfate, cobalt sulfate and zinc chloride.

[0062] In the present invention, the relative amount of the M source can be selected according to the amount of iron phosphate. According to some embodiments, the molar ratio of the M source to the iron phosphate is 0.005-0.025 in terms of M / Fe.

[0063] In some embodiments, the mass ratio of water to ferric phosphate may be (2-5):1, such as 2:1, 2.5:1, 3:1, and the like.

[0064] In some embodiments, the grinding is performed so that the particle size of the obtained slurry is 400-600 nm. The particle size can be measured by laser particle size method.

[0065] In the present invention, the drying may be, for example, spray drying.

[0066] In some embodiments, the first sintering is carried out under inert gas protection (e.g., nitrogen atmosphere), and the sintering temperature is 660-750°C, for example, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 730°C, 735°C, 740°C, 750°C; the first sintering time can be 6-15h, for example, 6h, 7h, 8h, 8.5h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc.

[0067] [Cathode Material B]

[0068] In the present invention, the positive electrode material B is a lithium iron phosphate material with a carbon coating layer prepared by a liquid phase hydrothermal method. The positive electrode material B prepared by the liquid phase hydrothermal synthesis method has small grains, uniform phase and relatively stable structure.

[0069] In some embodiments, the method for preparing the positive electrode material B comprises:

[0070] (1) uniformly mixing a second lithium source, an iron source, a phosphorus source, a solvent containing water, and an optional M source to obtain a mixture, and adding an orientation regulator to the mixture for emulsification and mixing to obtain a premixed slurry;

[0071] (2) subjecting the premixed slurry to a high-pressure hydrothermal reaction to obtain a mixed slurry containing lithium iron phosphate materials;

[0072] After filtering and washing the mixed slurry, water is added and mixed evenly to obtain an aqueous slurry of lithium iron phosphate material;

[0073] (3) uniformly mixing the aqueous slurry, the second carbon source and the lithium supplementing agent, and drying to obtain a mixed dry powder;

[0074] (4) The mixed dry powder is subjected to a second sintering and crushed into powder to obtain the positive electrode material B.

[0075] In step (1), the second lithium source can be selected from various soluble lithium-containing compounds used in the preparation of lithium iron phosphate. From the perspective of easy availability of raw materials, the second lithium source is preferably at least one of lithium carbonate and lithium hydroxide.

[0076] In some embodiments, the iron source may be selected from one or more of ferrous oxalate, ferrous nitrate and ferrous sulfate.

[0077] In some embodiments, the phosphorus source is phosphoric acid.

[0078] In some embodiments, the solvent further comprises an alcohol. The alcohol may be a polyol. Preferably, the alcohol is ethylene glycol and / or diethylene glycol.

[0079] In step (1), the type of the M source is as described above and will not be repeated here.

[0080] In step (1), according to some embodiments, the molar ratio of the M source to the iron source (M / Fe) is 0.005-0.025.

[0081] In step (1), based on the total mass of the second lithium source, iron source and phosphorus source, the mass amount of the solvent can be 15%-35%, for example, 18%, 20%, 25%, 27%, 28%, 30%, etc.

[0082] In step (1), the difference in adsorption capacity of different crystal faces of the material to the orientation regulator can be used to control the growth of the crystal face to achieve directional regulation of the crystal face orientation. According to some embodiments, the orientation regulator is selected from one or more of sucrose, starch, oxalic acid, acetic acid, tetracarboxyphenylporphyrin and glucoside.

[0083] Preferably, the alignment regulator is tetracarboxyphenylporphyrin, starch, acetic acid and glucoside, and the mass ratio of tetracarboxyphenylporphyrin, starch, acetic acid and glucoside is 1:(2-10):(20-50):(5-15), for example, 1:5, 30:10.

[0084] In some embodiments, based on the mass of the mixture, the amount of the orientation regulator is 0.2%-0.6%, for example, 0.2%, 0.3%, 0.4%, 0.45%, 0.5%, 0.6%, etc.

[0085] In step (2), according to some embodiments, the conditions of the high-pressure hydrothermal reaction include: a pressure of 1.6-2.0 MPa, for example, 1.6 MPa, 1.8 MPa, 2.0 MPa; a reaction temperature of 180-230°C, for example, 180°C, 185°C, 190°C, 200°C, 205°C, 210°C, etc.; a reaction time of 2-5h, for example, 2h, 3h, 3.5h, 4h, 5h, etc.

[0086] In step (2), the washing is intended to remove by-products in the mixed slurry. Depending on the raw materials used, the by-products may include, for example, one or more of sulfates, phosphates, carbonates, nitrates, oxalates, oxides, complex salts, etc. As some examples, the solvent used for washing may be a mixture of ethylene glycol and water, wherein the volume content of ethylene glycol in the mixture may be 5%-20%, for example, 10%.

[0087] In step (3), the second carbon source can be selected from various carbon-containing organic substances. According to some embodiments, the second carbon source is selected from one or more of sucrose, starch and polyvinyl alcohol.

[0088] Preferably, the second carbon source is sucrose, starch and polyvinyl alcohol, and the mass ratio of sucrose, starch and polyvinyl alcohol is 10: (1-3): (2-5), for example 10: 2: 3. The combination of the three carbon sources can promote uniform coating of the carbon layer and obtain a favorable degree of graphitization in the second sintering.

[0089] In some embodiments, based on the total mass of the second lithium source, iron source and phosphorus source, the mass dosage of the second carbon source is 5%-15%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 13%, etc.

[0090] In step (3), the lithium supplement is intended to compensate for the loss of lithium element at high temperature during the sintering process. According to some embodiments, the lithium supplement is one or more of lithium dihydrogen phosphate, lithium carbonate and lithium hydroxide.

[0091] In some embodiments, based on the total mass of the second lithium source, the iron source and the phosphorus source, the mass amount of the lithium supplement is 1%-4%, for example, 1%, 2%, 3%, 4%, etc.

[0092] In step (3), the drying may be spray drying.

[0093] In step (4), preferably, the second sintering is carried out under inert gas protection (e.g., nitrogen atmosphere), and the temperature of the second sintering is 680-730°C, for example, 680°C, 700°C, 710°C, 715°C, 720°C, 730°C, etc.; the sintering time is 3-10h, for example, 3h, 5h, 5.5h, 6h, 7h, 8h, 9h, 10h, etc.

[0094] In the present invention, the mass ratio of the positive electrode material A to the positive electrode material B is 100:(10-20), such as 100:10, 100:12, 100:13, 100:14, 100:15, 100:16, 100:17, 100:18, 100:19, 100:20, etc. The positive electrode material A can promote the performance of impedance during discharge, and the positive electrode material B can adjust the relative proportion of the lithium-rich phase and the lithium-poor phase during charge and discharge, and play a regulating role on the charging impedance.

[0095] In the present invention, the positive electrode material A and the positive electrode material B can be uniformly stirred in a high-speed mixer to obtain a mixed dry powder. Sintering the mixed dry powder can repair the damage to the carbon layer on the surface of the material that may be caused during the stirring process of the high-speed mixer.

[0096] In some embodiments, the sintering is performed under inert gas protection (such as nitrogen atmosphere), and the co-sintering temperature is 400-700° C., such as 400° C., 450° C., 480° C., 500° C., 550° C., 600° C., 650° C., 700° C., etc. In this way, while repairing the carbon layer, the possibility of the lithium iron phosphate material generating impurities is reduced.

[0097] In addition, the sintering time may be 1-5 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, etc.

[0098] The third aspect of the present invention provides a lithium battery, comprising the lithium battery positive electrode material according to the first aspect of the present invention. In some embodiments, the lithium battery is a lithium ion battery.

[0099] Generally, the lithium battery may include a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which can prevent the positive and negative electrodes from short-circuiting and allow ions to pass through.

[0100] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, and the positive electrode film layer contains the lithium battery positive electrode material.

[0101] In the present invention, in addition to the lithium battery positive electrode material, the positive electrode film layer may also include a binder, such as polyvinylidene fluoride (PVDF).

[0102] In some embodiments, the positive electrode film layer further comprises a conductive agent, for example, one or more selected from superconducting carbon, acetylene black, carbon black, carbon nanotubes and graphene.

[0103] In some embodiments, the positive electrode plate further comprises a positive electrode current collector, and the positive electrode film layer is disposed on at least one surface of the positive electrode current collector. The positive electrode current collector may be aluminum foil or carbon-coated aluminum foil.

[0104] In some embodiments, the negative electrode plate may be a lithium plate.

[0105] In some other embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be a metal current collector, such as copper foil.

[0106] In the present invention, the negative electrode film layer may include a negative electrode active material. The negative electrode active material is well known in the art and is not particularly limited in the present invention, for example, at least one selected from the following materials: graphite, soft carbon, hard carbon, silicon-based material, lithium titanate, etc.

[0107] In some embodiments, the negative electrode film layer further comprises a binder, and the binder used in the negative electrode is, for example, at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylamide and carboxymethyl cellulose.

[0108] In some embodiments, the negative electrode film layer further includes a conductive agent, for example, one or more of the following materials may be selected: superconducting carbon, acetylene black, carbon black, graphene, carbon nanotubes, etc.

[0109] In the present invention, the electrolyte can be selected with reference to existing lithium batteries. Generally, the electrolyte contains an organic solvent and an electrolyte lithium salt. Specific examples of the electrolyte salt include, but are not limited to, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, bisfluorosulfonyl imide, and the like. Specific examples of the organic solvent include, but are not limited to, ethyl methyl carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl formate, methyl acetate, propyl acetate, methyl propionate, ethyl propionate, and the like.

[0110] In the present invention, the separator may be any porous structure separator known in the art, and the material of the separator may be polyethylene, polypropylene, polyvinylidene fluoride, etc.

[0111] The lithium battery of the present invention may include a battery cell form, a battery module form, and a battery pack form.

[0112] The following are examples of the present invention. The following examples are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0113] Comparative Example 1

[0114] 500g of iron phosphate, 125g of lithium carbonate, 5.0g of vanadyl sulfate, 41.25g of glucose, 13.29g of PEG6000 and 1.25kg of water were added to a stirring tank and mixed evenly, and then ground to 500nm by a sand mill. After spray drying, the mixture was sent to a sintering furnace and sintered at 730℃ for 8h under a nitrogen atmosphere to obtain vanadium-doped lithium iron phosphate (LiFe 0.995 V 0.005 (PO4) / C), denoted as positive electrode material A1.

[0115] Comparative Example 2

[0116] (1) 3.6 kg of lithium hydroxide, ferrous sulfate, and phosphoric acid were weighed and mixed with 1.0 kg of a solvent (ethylene glycol and water in a volume ratio of 20:100) in a Li / Fe / P molar ratio of 3:1:1.01 to obtain a mixture;

[0117] Adding the mixed material and the orientation regulator into an emulsifier for emulsification and mixing to obtain a premixed slurry;

[0118] (2) adding the premixed slurry into a high-pressure reactor, and performing a high-pressure hydrothermal reaction at 1.8 MPa and 200° C. for 3.5 h to obtain a mixed slurry containing lithium iron phosphate;

[0119] The mixed slurry was filtered, washed with a mixture of ethylene glycol and water with a volume concentration of 10%, and then added with a proper amount of water and stirred evenly to obtain a lithium iron phosphate slurry with a solid content of 30%.

[0120] (3) The lithium iron phosphate slurry, the second carbon source and the lithium supplement agent are mixed, stirred evenly and then spray-dried to obtain a mixed dry powder.

[0121] (4) The mixed dry powder was added into a sintering furnace, sintered at 730° C. for 7 h in a nitrogen atmosphere, and the sintered product was crushed by gas crushing to obtain lithium iron phosphate with a carbon coating layer (chemical formula LiFePO / C), which was recorded as positive electrode material B1.

[0122] The amounts of main raw materials used in Comparative Example 2 are shown in Table 1.

[0123] Table 1

[0124]

[0125] In step (1), the amount of the orientation regulator added is calculated based on the weight of the mixture.

[0126] In step (3), the added amounts of the second carbon source and the lithium supplement are calculated based on the total mass of the phosphorus source, the iron source and the second lithium source.

[0127] Comparative Example 3

[0128] 500g of iron phosphate, 125g of lithium carbonate, 40g of glucose, 10g of PEG6000 and 1.23kg of water were added to a stirring tank and mixed evenly, and then ground to 500nm by a sand mill. After spray drying, the mixture was sent to a sintering furnace and sintered at 700°C for 12h under a nitrogen atmosphere to obtain lithium iron phosphate (LiFePO / C) with a carbon coating layer, which was recorded as positive electrode material A2.

[0129] Comparative Example 4

[0130] The positive electrode material was prepared according to the method of Comparative Example 2, except that the sintering temperature was adjusted to 680° C. The prepared lithium iron phosphate material with a carbon coating layer was recorded as positive electrode material B2.

[0131] Example 1

[0132] The positive electrode material A1 and the positive electrode material B1 were uniformly mixed in a high-speed mixer at a mass ratio of 100:10 to obtain a mixed dry powder, and the mixed dry powder was added into a sintering furnace and sintered at 450° C. for 3 hours in a nitrogen atmosphere to obtain a lithium battery positive electrode material.

[0133] Example 2

[0134] The positive electrode material A1 and the positive electrode material B1 were uniformly mixed in a high-speed mixer at a mass ratio of 100:20 to obtain a mixed dry powder, and the mixed dry powder was added into a sintering furnace and sintered at 650° C. for 2 hours in a nitrogen atmosphere to obtain a lithium battery positive electrode material.

[0135] Example 3

[0136] The positive electrode material A1 and the positive electrode material B1 were uniformly mixed in a high-speed mixer at a mass ratio of 100:15 to obtain a mixed dry powder. The mixed dry powder was added into a sintering furnace and sintered at 500° C. for 3 hours in a nitrogen atmosphere to obtain a lithium battery positive electrode material.

[0137] Comparative Example 5

[0138] The positive electrode material A1 and the positive electrode material B1 were uniformly mixed in a high-speed mixer at a mass ratio of 100:5 to obtain a mixed dry powder. The mixed dry powder was added into a sintering furnace and sintered at 450° C. for 3 hours in a nitrogen atmosphere to obtain a lithium battery positive electrode material.

[0139] Example 4

[0140] The positive electrode material A1 and the positive electrode material B2 were uniformly mixed in a high-speed mixer at a mass ratio of 100:12 to obtain a mixed dry powder, and the mixed dry powder was added into a sintering furnace and sintered at 500° C. for 4 hours in a nitrogen atmosphere to obtain a lithium battery positive electrode material.

[0141] Example 5

[0142] The positive electrode material A2 and the positive electrode material B2 were uniformly mixed in a high-speed mixer at a mass ratio of 100:17 to obtain a mixed dry powder, and the mixed dry powder was added into a sintering furnace and sintered at 500° C. for 4 hours in a nitrogen atmosphere to obtain a lithium battery positive electrode material.

[0143] Test Example 1

[0144] This test example is used to illustrate the differential XRD spectra and characteristic peak area acquisition methods of the lithium battery positive electrode materials of the above embodiments and comparative examples. Two groups of identical button-type half-cells were prepared for each lithium battery positive electrode material.

[0145] 1. Preparation of button half-cell

[0146] The positive electrode material of lithium battery, conductive agent Super P and binder PVDF were weighed according to the mass ratio of 9:0.4:0.6, and then stirred and mixed with solvent NMP. The slurry was adjusted in a degassing machine to control the viscosity of the slurry to 8000mPa·s. Then, the slurry was evenly coated on the carbon-coated aluminum foil by an automatic coating machine to form an original electrode sheet, which was placed in a vacuum oven at 130°C for 4 hours and then placed in a blast oven at 80°C for 12 hours to obtain a test piece.

[0147] Use a punching die with a diameter of 14 mm to cut out several small electrode sheets at different positions of the above test piece, select small electrode sheets with regular morphology, smooth surface and edges, weigh them with a 1 / 10,000 balance to determine the amount of positive electrode material used for the electrode sheet, put the weighed small electrode sheets into a vacuum drying oven, evacuate to 0.1 MPa, dry for 12 hours, obtain positive electrode sheets, and store them for later use;

[0148] In an inert gas glove box where the mass contents of water and oxygen are both less than or equal to 0.0005%, the battery is assembled according to the battery specification of CR2023; wherein the negative electrode is a lithium sheet, the separator is a polypropylene film, the electrolyte is a 1M lithium hexafluorophosphate solution (the solvent is a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1), and after the assembly is completed, it is packaged at 800Pa for 5s to obtain a button half-cell.

[0149] 2. Differential XRD spectrum test

[0150] (a) Each battery was charged and discharged for the first cycle at 25°C. The specific process was as follows: at 25°C, it was charged at a constant current rate of 0.1C to 4.2V (vs Li), charged at a constant voltage at a potential of 4.2V (vs Li) to a cutoff rate of 0.02C, and discharged at a constant current rate of 0.1C to 2.5V (vs Li).

[0151] (b) The test sample was charged at a constant current of 0.1C to a cut-off voltage of 4.2V (vs Li), and then charged at a constant voltage of 4.2V (vs Li) to a cut-off rate of 0.02C;

[0152] Then, one group of the batteries was discharged at a constant current of 0.1C rate to 50% SOC, while the other group of batteries was discharged at a constant current of 0.1C rate to 0% SOC.

[0153] (c) After the charge adjustment is completed, the button cell is disassembled within 30 minutes to remove the positive electrode sheet to be tested, and it is cleaned with EMC for 10 minutes, vacuum dried at room temperature for 30 minutes, and the positive electrode sheet is subjected to XRD test.

[0154] The XRD test of the pole piece was carried out on the Bruker D8 ADVANCE equipment, using Cu-kα as the radiation source. The pole piece to be tested was placed on a dedicated sample stage to ensure that the sample height was consistent with the sample holder. The sample test conditions were: Angle range: 10°-80°, step length The dwell time for each step is 0.3s. The XRD patterns of each electrode are obtained by testing.

[0155] (d) The XRD spectrum of the electrode is background-subtracted and normalized, and then the XRD spectrum of the electrode in the 50% SOC state and the XRD spectrum of the electrode in the 0% SOC state are subtracted to obtain the differential XRD spectrum of the corresponding material to be tested.

[0156] Specifically, open the TOPAS software, import the tested XRD spectrum into the software; select the sample batch that needs to calculate the differential XRD spectrum, first perform background subtraction, select the background fitting parameter (Background), and change the polynomial series Order setting to 4; then import the instrument parameters in the instrument parameter (Instrument) task bar; check the Sampledisplacement (sample height correction) in the error correction parameter (Corrections). The XRD spectrum after background subtraction is normalized to obtain the differential XRD spectrum, and then each characteristic peak is segmented and summed to calculate the peak area of ​​the characteristic peak in the differential XRD spectrum.

[0157] The differential XRD patterns of Example 1-2 and Comparative Example 1-2 are as follows: Figures 1 to 4 As shown, the boxes in each figure show various characteristic peaks between 17.0-17.5° and 18.0-18.3°, between 20.5-21.1°, and between 25.4-26.2°. Figures 1 to 4 It can be seen that in the differential XRD spectrum, the positive electrode material A1 ( Figure 3 ) The relative intensities of the characteristic peaks between 17.0-17.5° and 18.0-18.3°, between 20.5-21.1°, and between 25.4-26.2° are higher than those of the positive electrode material B1 ( Figure 4 ), and 10% ( Figure 1 )、20%( Figure 2 ) of the positive electrode material B1, the peak intensity and area of ​​each characteristic peak of the material in the above-mentioned region were effectively adjusted.

[0158] The absolute value test results of the characteristic peak areas in the differential XRD spectrum are shown in Table 2.

[0159] Table 2

[0160]

[0161]

[0162] The A / B mass ratio refers to the mass ratio of positive electrode material A and positive electrode material B used in the positive electrode material of a lithium battery.

[0163] Test Example 2

[0164] This test example is used to illustrate the ratio of the charging and discharging DCR of the lithium battery positive electrode materials prepared in the above comparative examples and examples, indicating the balanced performance characteristics of charging and discharging. Specifically including:

[0165] 1. Battery preparation

[0166] A button-type half-cell was assembled according to the method provided in Test Example 1.

[0167] 2. DCR performance test

[0168] (1) Perform the necessary first cycle charge and discharge on the battery according to the method provided in Test Example 1;

[0169] (2) Using a battery performance tester with a potential accuracy of 0.3 mV, discharge the button cell at a constant current rate of 0.1C to 50% SOC at 25°C, let it stand for 1 hour, and record the actual open circuit potential value of the button cell, which is calculated as V0; set the rate to 1.0C for constant current pulse discharge, the pulse time is 60 seconds, and record the instantaneous potential value at 18 seconds, which is calculated as V 18s ; Set the rate to 0.1C for constant current charging, the time is 600s, adjust the button battery state to 50% SOC, let it stand for 1h, record the actual open circuit potential value of the button battery, counted as V'0, set the rate to 1.0C for constant current pulse charging, the pulse time is 60s, record the instantaneous potential value at 10s, counted as V' 10s ;

[0170] According to the following DCR calculation formula, the DCR of discharging for 18s and charging for 10s are calculated respectively:

[0171] DCR=(V 0s -V ns ) / i, where

[0172] V 0s Indicates V0, V ns Indicates V 18s (DCR at 18s discharge), or

[0173] V 0s Indicates V'0, V ns V' 10s (DCR when charging for 10 seconds);

[0174] i represents the actual current at 1.0C rate.

[0175] The test results are shown in Table 3.

[0176] Table 3

[0177]

[0178] The charge-discharge ratio is the ratio of the DCR for charging for 10s to the DCR for discharging for 18s.

[0179] Combining the test results of Table 2 and Table 3, it can be seen that compared with Comparative Examples 1-5, in the differential XRD spectra of the lithium battery positive electrode materials provided in Examples 1-5, the sum of the absolute values ​​of the characteristic peak areas between 17.0-17.5° and 18.0-18.3° is 0.043-0.060, the sum of the absolute values ​​of the characteristic peak areas between 20.5-21.1° is 0.030-0.065, and the sum of the absolute values ​​of the characteristic peak areas between 25.4-26.2° is in the range of 0.050-0.090. The positive electrode materials that meet the above ranges can effectively solve the problem of large differences in DCR impedance of lithium iron phosphate under the same SOC state during battery charging and discharging. Specifically, compared with comparative examples 1-5, the charge-discharge ratio of embodiments 1-5 is reduced from about 1.16 to about 1.1, so that the charging and discharging performance of the positive electrode material is balanced: when the discharge impedance is reduced, the charging impedance can also be reduced to the same level, thereby reducing the battery energy consumption during discharge and charging at the same time, improving polarization heat generation, and thus improving the charging safety of the lithium battery.

[0180] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A positive electrode material for a lithium battery, characterized in that: A lithium iron phosphate material having a carbon coating layer, wherein in a differential XRD spectrum of the lithium battery positive electrode material, the sum of the absolute values ​​of the peak areas of the characteristic peaks between 17.0-17.5° and 18.0-18.3° is 0.043-0.060, the sum of the absolute values ​​of the peak areas of the characteristic peaks between 20.5-21.1° is 0.030-0.065, and the sum of the absolute values ​​of the peak areas of the characteristic peaks between 25.4-26.2° is 0.050-0.090; The method for obtaining the differential XRD spectrum is: S1, assembling the positive electrode sheets containing the positive electrode material of the lithium battery into two groups of batteries, namely battery I and battery II; S2, at 25°C, charge and discharge the battery I and the battery II for the first cycle, and continue to charge to 100% SOC, then discharge the battery I to 50% SOC, and discharge the battery II to 0% SOC, to obtain the battery I and the battery II after load adjustment; S3, performing XRD tests on the positive electrode plates in the battery I and the battery II after charge adjustment, respectively, to obtain XRD spectra of the plates; S4, performing background subtraction and normalization processing on the pole piece XRD spectrum, subtracting the pole piece XRD spectrum of battery I from the pole piece XRD spectrum of battery II to obtain a differential XRD spectrum.

2. The positive electrode material for lithium battery according to claim 1, characterized in that: In step S1, the two assembled battery groups are half button batteries; The operation of step S3 includes: disassembling the battery I and the battery II after charge adjustment to obtain the positive electrode sheet, washing the positive electrode sheet with an organic solvent, vacuum drying, and performing an XRD test; Preferably, the organic solvent is at least one of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, propylene carbonate and ethylene carbonate; Preferably, the vacuum drying temperature is 20-40°C.

3. The positive electrode material for lithium battery according to claim 1 or 2, characterized in that: The chemical formula of the lithium iron phosphate material is LiFe x M 1-x PO4, 0.98≤x≤1.0, M is selected from one or more of Mn, F, Al, Ti, Zr, Co, Zn and V; Preferably, the lithium iron phosphate material is LiFePO4 and LiFe 0.995 V 0.005 (PO) or more.

4. The positive electrode material for a lithium battery according to any one of claims 1 to 3, characterized in that: In the differential XRD spectrum of the lithium battery positive electrode material, the sum of the absolute values ​​of the peak areas of the characteristic peaks between 17.0-17.5° and 18.0-18.3° is 0.043-0.055, the sum of the absolute values ​​of the peak areas of the characteristic peaks between 20.5-21.1° is 0.032-0.058, and the sum of the absolute values ​​of the peak areas of the characteristic peaks between 25.4-26.2° is 0.051-0.

085.

5. The method for preparing the positive electrode material for a lithium battery according to any one of claims 1 to 4, characterized in that: include: The positive electrode material A and the positive electrode material B are mixed and sintered in a mass ratio of 100:(10-20) to obtain the positive electrode material for a lithium battery; wherein, The positive electrode material A is a lithium iron phosphate material with a carbon coating layer prepared by a solid phase method. The positive electrode material B is a lithium iron phosphate material with a carbon coating layer prepared by a liquid phase hydrothermal method.

6. The preparation method according to claim 5, characterized in that: The sintering is carried out under the protection of an inert gas, the sintering temperature is 400-700° C., and the sintering time is 1-5 hours.

7. The preparation method according to claim 5 or 6, characterized in that: The method for preparing the positive electrode material A comprises: uniformly mixing iron phosphate, a first lithium source, a first carbon source, water and an optional M source, grinding, drying, and then performing a first sintering to obtain the positive electrode material A; wherein, The M source is selected from one or more of a Mn source, a F source, an Al source, a Ti source, a Zr source, a Co source, a Zn source and a V source; Preferably, the first lithium source is selected from lithium carbonate and / or lithium hydroxide; Preferably, the first carbon source is selected from glucose and / or polyethylene glycol; Preferably, the mass ratio of the first carbon source to iron phosphate is (8-15):100; Preferably, the first sintering is performed under the protection of an inert gas, the temperature of the first sintering is 660-750° C., and the time is 6-15 hours.

8. The preparation method according to claim 5 or 6, characterized in that: The method for preparing the positive electrode material B comprises: (1) uniformly mixing a second lithium source, an iron source, a phosphorus source, a solvent containing water, and an optional M source to obtain a mixture, and adding an orientation regulator to the mixture for emulsification and mixing to obtain a premixed slurry; Wherein, the M source is selected from one or more of a Mn source, a F source, an Al source, a Ti source, a Zr source, a Co source, a Zn source and a V source; (2) subjecting the premixed slurry to a high-pressure hydrothermal reaction to obtain a mixed slurry containing lithium iron phosphate materials; The mixed slurry is filtered and washed, and then water is added to mix evenly to obtain an aqueous slurry of lithium iron phosphate material; (3) uniformly mixing the aqueous slurry, the second carbon source and the lithium supplementing agent, and drying to obtain a mixed dry powder; (4) subjecting the mixed dry powder to a second sintering step and crushing and powdering to obtain the positive electrode material B; Preferably, the second lithium source is selected from lithium carbonate and / or lithium hydroxide; Preferably, the iron source is selected from one or more of ferrous oxalate, ferrous nitrate and ferrous sulfate; Preferably, the phosphorus source is phosphoric acid.

9. The preparation method according to claim 8, characterized in that: The orientation regulator is selected from one or more of sucrose, starch, oxalic acid, acetic acid, tetracarboxylphenylporphyrin and glucoside; Preferably, based on the mass of the mixture, the mass amount of the orientation regulator is 0.2%-0.6%; Preferably, the pressure of the high-pressure hydrothermal reaction is 1.6-2 MPa, the temperature is 180-230° C., and the time is 2-5 h; Preferably, the second carbon source is selected from one or more of glucose, sucrose, starch and polyvinyl alcohol; Preferably, based on the total mass of the second lithium source, the iron source and the phosphorus source, the mass amount of the second carbon source is 5%-15%; Preferably, the lithium supplement is selected from one or more of lithium dihydrogen phosphate, lithium carbonate and lithium hydroxide; Preferably, based on the total mass of the second lithium source, the iron source and the phosphorus source, the mass amount of the lithium supplement agent is 1%-4%; Preferably, the solvent further comprises alcohol, more preferably the alcohol is ethylene glycol and / or diethylene glycol; Preferably, the second sintering is performed under the protection of an inert gas, the temperature of the second sintering is 680-730° C., and the time is 3-10 hours.

10. A lithium battery, characterized in that: The lithium battery positive electrode material comprises any one of claims 1 to 4.